Neighbourhood change, deprivation, and unemployment in Belfast. Issue 2 (1st December 2021) - Lloyd, Christopher D.
Abstract: Much effort has been expended on measuring deprivation in neighbourhoods across the UK and elsewhere. However, there has been only a relatively limited concern with deprivation histories of areas. This paper takes as its focus Belfast in Northern Ireland and it capitalises on rich data sources on deprivation generally and unemployment specifically. The study makes use of data on multiple time points – the Census from 1971 to 2011, multiple deprivation measures for 2005, 2010, and 2017, and benefits claimant count data for 2020. The paper explores the changing geography of deprivation and unemployment, identifying areas with persistently high deprivation and unemployment across time and across measures. It is argued that trajectories are important, particularly in terms of targeting resources. The final section of the analysis uses claimant count data to assess changing unemployment rates following the outbreak of the COVID‐19 pandemic and it shows that changes in these rates are strongly related to long‐term deprivation and unemployment patterns. Abstract : The paper explores the geographies of deprivation and unemployment change in Belfast. Population characteristics associated with unemployment risk and job losses following COVID‐19 lockdown are identified. The paper concludes by arguing that it is essential to consider area histories in designing schemes to tackle deprivation.